Artificial intelligence in the pediatric echocardiography laboratory: Automation, physiology, and outcomes - Nguyen, Minh B.; Villemain, Olivier; Friedberg, Mark K.; Lovstakken, Lasse; Rusin, Craig G.; Mertens, Luc (Frontiers in Radiology, 2022)
Artificial Intelligence (AI) is frequently used in non-medical fields to assist with automation and decision-making. The potential for AI in pediatric cardiology, especially in the echocardiography laboratory, is very high. There are multiple tasks AI is designed to do that could improve the quality, interpretation, and clinical application of echocardiographic data at the level of the sonographer, echocardiographer, and clinician. In this state-of-the-art review, we highlight the pertinent literature on machine learning in echocardiography and discuss its applications in the pediatric echocardiography lab with a focus on automation of the pediatric echocardiogram and the use of echo data to better understand physiology and outcomes in pediatric cardiology. We also discuss next steps in utilizing AI in pediatric echocardiography.